A dual fluorogenic and 19F NMR probe for the detection of esterase activity. (8th May 2018) - Hu, Jie; Cheng, Kai; Wu, Qiong; Ding, Dashuang; Li, Conggang; Li, Zhen
Abstract : A dual-channel probe ofFlE based on flavonoid derivatives was successfully designed and synthesized, which could yield "turn-on" signals of both fluorometry and 19 F nuclear magnetic resonance in response to the presence of esterase. Abstract : In this study, a dual-channel probe ofFlE based on flavonoid derivatives is reported, which can yield "turn-on" signals of both fluorometry and 19 F nuclear magnetic resonance in response to the presence of esterase. Upon the addition of esterase, FlE could convert intoFl, possessing the ESIPT effect. As a result, the fluorescence intensity was significantly enhanced and peaked at 510 nm, accompanying a change in the fluorescence of solution from nonluminous to strong green. Moreover, as determined by 19 F NMR, the signal could apparently shift from δ F −111.57 to −111.69 ppm. Due to the combination of these two detection approaches having good sensitivity, high selectivity, and real-time detection, FlE has been successfully applied to confocal fluorescence imaging for the detection of esterase in cells, which consistent with the 19 F NMR test results in some sense.